Initial sirolimus dosage recommendations for pediatric patients with PIK3CD mutation-related immunodeficiency disease - Chen, Xiao; Wang, Jinglin; Lan, Jianger; Ge, Xilin; Xu, Hong; Zhang, Yu; Li, Zhiping (Frontiers in Pharmacology, 2022)
Sirolimus has been used to treat pediatric patients with PIK3CD mutation related immunodeficiency disease. However, the initial dosages of sirolimus remain unknown. The present study aims to explore the initial dosages of sirolimus in pediatric patients with PIK3CD mutation related immunodeficiency disease. Pediatric patients with PIK3CD mutation related immunodeficiency disease were included to analyze using application of the population pharmacokinetic (PPK) model and Monte Carlo simulation. Body weight and concomitant use of posaconazole were included in the final PPK model, where under the same weight the clearances of sirolimus were 1 : 0.238 between children without posaconazole and children with posaconazole. Without posaconazole, the initial dosages of sirolimus were 0.07, 0.06, 0.05 and 0.04 mg/kg/day for body weights of 10-14, 14-25, 25-50 and 50-60 kg in children with PIK3CD mutation related immunodeficiency disease. With posaconazole, the initial dosages of sirolimus were 0.02 mg/kg/day for body weights of 10-60 kg in children with PIK3CD mutation related immunodeficiency disease. It was the first time to build up a sirolimus PPK model meanwhile recommend the initial dosages in children with PIK3CD mutation related immunodeficiency disease, providing a reference for clinical individualized drug administration.